26th Annual Conference of the International Group for Lean Construction 2018
DOI: 10.24928/2018/0452
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effectiveness of Visual Management Best Practices in Construction Sites

Abstract: Visual Management (VM) is a strategy for information management strongly related to one of the core concepts of Lean Production Philosophy, the increase of process transparency. VM is especially important to support continuous improvement and it relies on the effective transmission of information at different hierarchical levels. However, there are some challenges in the implementation of VM in construction: each construction project is unique, site layouts are dynamic environments, and the construction itself… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Visual management on a construction site is not limited to visual boards, it also encompasses visual aids in the environment (Brady et al 2012;Brandalise et al 2018;Farzad and Cameron 2019;Reinbold et al 2020;Tezel et al 2016;Tezel et al 2011;Valente et al 2016;Wesz et al 2018), our focus here is on VM production boards or models. According to Tezel et al (2016), VM has nine functions in total, mentioned here below;…”
Section: Visual Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual management on a construction site is not limited to visual boards, it also encompasses visual aids in the environment (Brady et al 2012;Brandalise et al 2018;Farzad and Cameron 2019;Reinbold et al 2020;Tezel et al 2016;Tezel et al 2011;Valente et al 2016;Wesz et al 2018), our focus here is on VM production boards or models. According to Tezel et al (2016), VM has nine functions in total, mentioned here below;…”
Section: Visual Managementmentioning
confidence: 99%
“…The literature review made it evident that multiple case studies present implementation of VM in numerous expressions and also in relation to different planning methods such as Takt at operators level in modular construction , Mariz et al (2019) used VM to visualize Kanban for planning the construction of a dam. (Brandalise et al 2018) used VM for Kanban combined with a performance board, where Farzad and Cameron (2019) used it for deliverable matrixes. Wesz et al (2018) presented a complete project VM adaption of Last Planner System (LPS) (Ballard 2000), and Mota et al (2019) instead defined the VM as part of the collaborative planning alone.…”
Section: Introductionmentioning
confidence: 99%
“…VM is formed by a combination of Visual Metrics and Visual Controls (VC) into easily digestible information with little to no training to understand. VM consists of fairly simple visual practices, such as boards that contain procedure information, production drawings, or performance metrics (Brandalise et al, 2018;, and more advanced practices requiring planning and stability within the production system (Brandalise et al, 2018;. Lewinski (2018) indicated that VM should include its maximum range of the company's operation to take of all its advantage.…”
Section: Visual Management (Vm) and Visual Control (Vc)mentioning
confidence: 99%
“…The use of VM devices like Kanban, Poka-yoke and Andon systems to solve construction problems due to a lack of flow understanding and reduced process transparency due to physical borders (walls and piles of materials) has been widely studied; several studies have reported successful results (e.g., Tezel et al 2010;Biotto et al 2014;Bascoul et al 2017;Brandalise et al 2018).…”
Section: Literature Review Visual Managementmentioning
confidence: 99%